Impact of Electronic Agreements from the Viewpoint of the Indonesian Civil Code - Indrati Rini; Soesi Idayanti (International Journal of Science and Society, 2021)
There are often legal problems, both concerning issues of authenticity, authenticity and proof because there is no law that specifically regulates personal data of agreement users via electronic means. The problem raised is how the problem of the authenticity, authenticity and integrity of the agreement electronically and how the validity of an agreement made electronically. The research method that the author uses is normative qualitative by using secondary data and reinforced by primary data or field data. The results of the study show that the authenticity, authenticity and integrity of the agreement electronically can be carried out using digital forensic tools. The use of information through electronic media concerning a person's personal data must be carried out with the consent of the person concerned. Agreements made electronically/digitally have the same evidentiary power as agreements made through manuals. Judges can use the evidentiary system with the development towards open evidence. Evidence obtained from anywhere as long as the truth can be accepted as long as it does not conflict with public order, considering that in conducting transactions in the current digital era, we will often use online media.